MTKM di Indonesia Efektivitas Mekanisme Transmisi Kebijakan Moneter di Indonesia Melalui Jalur Kredit - setyoadi ambudi; Evita Novilia; Achmad Asrofi; Ruth Eviana (Universitas Nahdlatul Ulama Blitar, 2022)
The aim of this study is to see how effective the monetary policy transmission mechanism is through the interest rate channel in Indonesia. This research was conducted to see how effective the monetary policy transmission mechanism is through the interest rate channel using data from 197 – 2017. This research uses the Vector Autoregression (VAR) method in its testing process. The results of this study indicate that the credit channel is an effective channel for achieving the ultimate goal of monetary policy in Indonesia.